Некоторые особенности формирования половых клеток у самцов американской белой бабочки (Hyphantria cunea Dr.) - Богач, А.В. (Вестник зоологии, 1974)
Morphology and histological structure of Hyphantria cunea Dr. gonads are studied. The processes of spermatogenesis are investigated at all the postembryonic stages of de- velopment. The process of sex cells formation and gonads growth are established to acce- lerate from the caterpillars of the IV age. Spermatogenesis in Hyphantria curea Dr. proceeds according to the type common to Lepidoptera. However in Hyphantria cunea Dr. at the pupa stage the paired gonads fuse into one, that is not observed in Bombyx mori L. and Antheraca pernyi G.-M.